Uzbekistan as a tourist destination for creating new projects (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
Uzbekistan is a country of the greatest cities with hundreds of architectural monuments of different eras. Samarkand, Bukhara, Khiva, Shakhrisabz, Termez and Kokand are known throughout the world. These cities, the same age as Rome and Babylon, were once the largest centers of science and culture. The best minds and hands of that time flocked to them. The world was amazed by the luxury and splendor of palaces, minarets, mosques, and mausoleums created by famous architects of the past. World-famous monuments of ancient architecture still remember the times of the conquests of Alexander the Great and Genghis Khan where anyone can create new project based on tourism